Municipal solid waste management instruments that influence the use of the refuse as fuel in developing countries A critical review - Galavote, Tânia (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2025)
Landfills are the destination of most of the refuse generated whereas composting, material recycling, and Waste-to-Energy (WtE) technologies are not commonly employed in developing countries. However, the destination for energy purposes could be supplied with this refuse, improving the viability of energy use. Thus, this article raises some questions to identify aspects that could encourage its use as refuse-derived fuel (RDF) in these countries. Among them, does environmental education affect the municipal solid waste (MSW) source separation with emphasis on a destination? Can selective collection and extended producer responsibility (EPR) affect the MSW for energy recovery? Is there competition between the recycling market and the energy market for RDF? A systematic review of the literature was conducted to gather data and provide answers to such questions. This enabled to observe that EPR, selective collect expansion and source separation influence the quantity and quality of waste sent for energy use. Both internal and external factors impact on source separation. Additionally, there is evidence to support that despite several studies showing their technical, economic, environmental and social viability, the methods of energy usage of the refuse still need to improve their deployment in developing countries. In addition to identifying the main research gaps to be filled in future studies, the article also identified the instruments of MSW management that are to be applied in developing countries to divert recyclable and organic waste from landfill